PHYSIOLOGICAL AND GROWTH RESPONSE OF TOMATO PLANTS AFTER TRICHODERMA SPP. SEED TREATMENTS - PETRISOR, Cristina; PAICA, Alexandru; BURNICHI, Floarea (Studia Universitatis Babeș-Bolyai Chemia, 2019)
Different isolates of Trichoderma are able to produce metabolites which induce some morphological and physiological changes in plant such as enhanced plant growth and response to plant pathogens or reduced plant stress. The aim of the present study is to evaluate the effect of some Trichoderma isolates on plant growth promoting and physiological parameters of tomato plants. Also, the Trichoderma isolates were assessed based on IAA (indole 3-acetic acid) production and ability to solubilize phosphate, traits associated to growth. Tomato seed treatment with Trichoderma isolates led to a significant increase in plant height as well as root length and root fresh/ dry weight. However, metabolite production varied among isolates and depends on the isolate. Our data indicated that three of the Trichoderma isolates studied increase leaf pigments content and improve the photosynthetic activity of tomato plants.